EFEKTIFITAS PELAKSANAAN SISTEM BLOK PADA PEMBELAJARAN TEACHING FACTORY DI SMK - Gatiningsih, Widya (Universitas Negeri Surabaya, 2020)
Abstract Block system was a learning system that organized or classified the learning hours into longer than usual to make the students could learnt more optimally. In vocational high schools (SMK), the block system could be implemented through teaching factory learning as an effort to increase the effectiveness of learning. Teaching factory was a learning that oriented in a production adjusted with competency of proficiency in their fields.The goal of this study was to : (1) knowing the implementation of block system in SMK, (2) knowing the effectiveness in implementating block system in term of learning, educators, students, and practicum equipment, (3) knowing the effectiveness in implementating block system into teaching factory learning. This study was literature review by searching teori referention relevant with problem or case found and explained about the effectiveness in implementating of block system. The result of this literature review study shown that : (1) the implementation of block system in SMK was succesful with overall average results 65,90%; (2) the effectiveness in implementating block system in term of learning, educators, students, and practicum equipment which shown the high category with overall average result 60% which means it was very effectively applied in vocational high school as an effort to increase the learning quality; (3) there was significant influence between of the competency scores of the student that used block system with the students that used non - block system which is 84.171 in teaching factory learning. Keywords: effectiveness, block system, teaching factory.